Selected psychological factors in elite Greco-Roman wrestlers at various levels of competition - Rutkowska, K.; Gierczuk, D.; Buszta, M. (Journal of Physical Education and Sport, 2020)
Due to the deterioration in mental health in the societies and, in view of significant challenges of contemporary sport, it is necessary to carry out research on psychological factors and, based on research results, to hold interdisciplinary discussions about the role of mental preparation in sport. It is suggested that psychological resources, i.e. psychological factors that determine optimal performance in sport and in other activities not related to sport, should be enhanced. These factors include, inter alia, styles of coping with stress (coping styles) and achievement motivation. The aim of the study was to investigate selected psychological factors (including achievement motivation and coping styles) in wrestlers at various levels of competition. This study sought to explore selected psychological factors in wrestlers at various levels of competition. The study included elite Greco-Roman wrestlers from two age groups: juniors (n = 25) and seniors (n = 25). The first group consisted of athletes aged 16-18 and with training experience of 4 to 10 years. The other group was composed of athletes 19-26 years of age and with training experience of 5 to 17 years. CISS and LMI inventories were applied. Dimensions of achievement motivation and different coping styles were analysed. Compared to juniors, seniors exhibited more developed task-oriented coping style. Furthermore, they were more self-confident. In seniors, task-oriented coping style correlated positively with a general dimension of achievement motivation and self-confidence; however, emotion-focused coping style correlated negatively with a general level of achievement motivation and self-control. In addition, a negative correlation was noted between self-control, avoidance coping style and distraction. In juniors, achievement motivation and ambition correlated positively with task-oriented coping style. In the future, it would be useful to carry out longitudinal studies to check possible age- and experience-related changes in the use of certain coping styles as well as dimensions of achievement motivation in particular groups. The process of training in elite wrestlers requires constant cooperation with sports psychologists in terms of monitoring psychological variables (e.g. achievement motivation and coping styles) and, if necessary, implementing sport-specific mental training. Further research is needed to investigate psychological factors in wrestling more thoroughly. However, the data gathered may be used when developing mental training oriented at elite wrestlers.